2020
DOI: 10.21203/rs.3.rs-67820/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smartphone Usage and Pattern on Self-reported Symptoms Among Medical Students in Universiti Kebangsaan Malaysia During the COVID-19 Lockdown

Abstract: Background Smartphone ubiquitous has become profound especially during 2019 Coronavirus Disease (COVID-19) lockdown period. It is worth considering the influence on users’ health symptoms, which extend beyond the realm of communication. Prior research suggests smartphone’s usage and pattern correlated with self-reported symptoms from different countries. Hence, this research aimed to evaluate the smartphone usage and pattern, also its association on self-reported symptoms among medical students in Malaysia, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…1 During the COVID-19 pandemic, the importance of smartphone use has aggravated as of its multifunctional capacity integrating several functions such as information, communication, online education, entertainment, and so forth. 2 However, excessive and uncontrolled use of smartphones can be deleterious to psychological health, which was explored in the prior studies conducted during the normal time [see Sohn et al 3 for a recent systematic review].…”
Section: Introductionmentioning
confidence: 99%
“…1 During the COVID-19 pandemic, the importance of smartphone use has aggravated as of its multifunctional capacity integrating several functions such as information, communication, online education, entertainment, and so forth. 2 However, excessive and uncontrolled use of smartphones can be deleterious to psychological health, which was explored in the prior studies conducted during the normal time [see Sohn et al 3 for a recent systematic review].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on medical students in Malaysia during the COVID-19 pandemic, it was stated that the level of smartphone addiction increased, and the participants even used a smartphone or an additional device in the first 15 minutes after waking up (15). In our country (Turkey) in the other studies conducted on students' pandemic period of excessive use of smartphones (score 88.4), and that has been reported to correlate well with increased levels of nomophobia (16).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above [7] another hypothetical study conducted in which physiologic impacts of EMF exposures have frequently reported, exposure to EMF can cause this activation by producing more free radicals, there is a broad activation can explain the variety of effects that have been seen, free radicals are important components of phagocytosis as well as natural processes like mitochondrial metabolism, ionizing radiation or phorbol ester therapy can induce the release of free radicals, resulting in chromosomal instability in both. The following are some of the acute and long-term impacts of EMF exposure that are mediated by rising free radical levels.…”
Section: Givenmentioning
confidence: 97%